2020
DOI: 10.3389/fbioe.2020.00222
|View full text |Cite
|
Sign up to set email alerts
|

Laccases in Food Industry: Bioprocessing, Potential Industrial and Biotechnological Applications

Abstract: Laccase is a multi-copper oxidase that catalyzes the oxidation of one electron of a wide range of phenolic compounds. The enzyme is considered eco-friendly because it requires molecular oxygen as co-substrate for the catalysis and it yields water as the sole by-product. Laccase is commonly produced by fungi but also by some bacteria, insects and plants. Due it is capable of using a wide variety of phenolic and nonphenolic substrates, laccase has potential applications in the food, pharmaceutical and environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(56 citation statements)
references
References 49 publications
0
40
0
3
Order By: Relevance
“…White-rot fungi, with the ability to degrade lignocellulosic material, are valued in the paper, textile, and food industries for their ability to produce various lignocellulosicdegrading enzymes [1][2][3]. These fungi differ from brown-rot in that they can degrade all lignocellulose constituents (lignin, cellulose, and hemicellulose) producing CO 2 as a byproduct of this metabolism [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…White-rot fungi, with the ability to degrade lignocellulosic material, are valued in the paper, textile, and food industries for their ability to produce various lignocellulosicdegrading enzymes [1][2][3]. These fungi differ from brown-rot in that they can degrade all lignocellulose constituents (lignin, cellulose, and hemicellulose) producing CO 2 as a byproduct of this metabolism [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Laccase has a great potential for integrating biotechnological processes in various industries, such as lignocellulosic biorefinery (including in the traditional pulp and paper industry), chemical, biomedical, and pharmaceutical industries. [ 92a , 92c ] Despite this, information on the current use of laccase for valorizing lignins on industrial scale is not easily found, likely due to the confidentiality that protects such processing conditions. On the other hand, some practical and technical aspects available in the literature published on laboratory‐scale experiments help to identify the challenges and opportunities regarding the current industrial use of laccases.…”
Section: Patented Applicationsmentioning
confidence: 99%
“…Despite this, the availability of stocks and the cost of laccases still raise certain concerns when their industrial use is discussed, especially when high‐purity enzyme is required. [ 92a , 112 ] In this sense, the invention of economic, safe, and efficient methods for producing microbial laccases is highly opportune. [113] Novel technologies can also benefit the development of biotechnical methods for enzyme production to increase laccase purity and stability.…”
Section: Patented Applicationsmentioning
confidence: 99%
“…Na indústria de alimentos, em especial, a utilização de lacases é realizada em produtos de panificação, laticínios, bebidas e ingredientes (síntese de novos compostos antioxidantes e antimicrobianos). Estas enzimas atuam na melhoria dos parâmetros sensoriais de alimentos, controle de odores, realce de sabor e novas funcionalidades, bem como para a remoção de compostos indesejáveis em certos produtos alimentícios, entre outras possibilidades (MAYOLO-DELOISA et al, 2020).…”
Section: Neste Cenário As Espéciesunclassified